2014
DOI: 10.5937/mckg48-5357
|View full text |Cite
|
Sign up to set email alerts
|

Current experience and future perspectives of bromelain application in medicine

Abstract: Bromelain je sirov, vodeni ekstrakt stabljike i ploda ananasa (Ananas cosmus fam. Bromeliaceae) i predstavlja kompleksnu mešavinu različitih tiol endopeptidaza, raznovrsnih glikoliziranih enzimskih vrsta papainske superfamilije enzima koji imaju različitu proteolitičku aktivnost (1, 2). dobija se iz hladnog soka ananasa centrifugiranjem, ultrafiltracijom, liofilizacijom i drugim postupcima. Smatra se da je bromelain glikoprotein sastavljen od jednog polipeptidnog i jednog bočnog oligosaharidnog lanca koji je v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Bromelain is absorbed from the human intestines and maintains biological activity with a half-life of ~6-9 h (18). Research conducted in experimental animals has shown that bromelain has analgesic, antiedematous, anti-inflammatory, anticoagulant, immunomodulatory and hepatoprotective effects (19). However, the impact of bromelain, which is known to have antioxidant properties, on sperm quality and testis damage remains unknown.…”
mentioning
confidence: 99%
“…Bromelain is absorbed from the human intestines and maintains biological activity with a half-life of ~6-9 h (18). Research conducted in experimental animals has shown that bromelain has analgesic, antiedematous, anti-inflammatory, anticoagulant, immunomodulatory and hepatoprotective effects (19). However, the impact of bromelain, which is known to have antioxidant properties, on sperm quality and testis damage remains unknown.…”
mentioning
confidence: 99%